Far-infrared observations of an unbiased sample of gamma-ray burst host galaxies - Kohn, S.A.; Micha owski, M.J.; Bourne, N.; Baes, M.; Fritz, J.; Cooray, A.; de Looze, I.; De Zotti, G.; Dannerbauer, H.; Dunne, L.; Dye, S.; Eales, S.; et al. (Oxford University Press, 2015)
Gamma-ray bursts (GRBs) are the most energetic phenomena in the Universe; believed to result from the collapse and subsequent explosion of massive stars. Even though it has profound consequences for our understanding of their nature and selection biases, little is known about the dust properties of the galaxies hosting GRBs. We present analysis of the far-infrared properties of an unbiased sample of 20 BeppoSAX and Swift GRB host galaxies (at an average redshift of z = 3.1) located in the Herschel Astrophysical Terahertz Large Area Survey, the Herschel Virgo Cluster Survey, the Herschel Fornax Cluster Survey, the Herschel Stripe 82 Survey and the Herschel Multi-tiered Extragalactic Survey, totalling 880 deg2, or ∼3 per cent of the sky in total. Our sample selection is serendipitous, based only on whether the X-ray position of a GRB lies within a large-scale Herschel survey – therefore our sample can be considered completely unbiased. Using deep data at wavelengths of 100–500 μm, we tentatively detected 1 out of 20 GRB hosts located in these fields. We constrain their dust masses and star formation rates (SFRs), and discuss these in the context of recent measurements of submillimetre galaxies and ultraluminous infrared galaxies. The average far-infrared flux of our sample gives an upper limit on SFR of <114 M⊙ yr−1. The detection rate of GRB hosts is consistent with that predicted assuming that GRBs trace the cosmic SFR density in an unbiased way, i.e. that the fraction of GRB hosts with SFR > 500 M⊙ yr−1 is consistent with the contribution of such luminous galaxies to the cosmic star formation density.